Business Strategy Transformation: The Impact of Global Digitalization and COVID-19 Pandemic Factors - Ivanova, Nataliia; Nazarko, Svitlana; Denysenko, Tetana; Kublitska, Olena; Kononenko, Serhii (Journal of the University of Zulia, 2023)
<span dir="ltr" style="left: calc(var(–scale-factor)*56.66px); top: calc(var(–scale-factor)*284.14px); font-size: calc(var(–scale-factor)*12.96px); font-family: serif; transform: scaleX(1.03371);" role="presentation">The article aims to consider the business <span dir="ltr" style="left: calc(var(–scale-factor)*277.78px); top: calc(var(–scale-factor)*284.14px); font-size: calc(var(–scale-factor)*12.96px); font-family: serif; transform: scaleX(1.03512);" role="presentation">strategy transformation process <span dir="ltr" style="left: calc(var(–scale-factor)*449.93px); top: calc(var(–scale-factor)*284.14px); font-size: calc(var(–scale-factor)*12.96px); font-family: serif; transform: scaleX(1.05049);" role="presentation">in the context of <span dir="ltr" style="left: calc(var(–scale-factor)*56.66px); top: calc(var(–scale-factor)*300.94px); font-size: calc(var(–scale-factor)*12.96px); font-family: serif; transform: scaleX(1.00906);" role="presentation">global digitali<span dir="ltr" style="left: calc(var(–scale-factor)*129.89px); top: calc(var(–scale-factor)*300.94px); font-size: calc(var(–scale-factor)*12.96px); font-family: serif; transform: scaleX(1.02037);" role="presentation">zation and the COVID-<span dir="ltr" style="left: calc(var(–scale-factor)*253.78px); top: calc(var(–scale-factor)*300.94px); font-size: calc(var(–scale-factor)*12.96px); font-family: serif; transform: scaleX(1.01346);" role="presentation">19 pandemic in business and the economy. To achieve <span dir="ltr" style="left: calc(var(–scale-factor)*56.66px); top: calc(var(–scale-factor)*317.98px); font-size: calc(var(–scale-factor)*12.96px); font-family: serif; transform: scaleX(1.05284);" role="presentation">the goal, the authors analyzed the notions of "IT strategy", "digital strategy" and "digital <span dir="ltr" style="left: calc(var(–scale-factor)*56.66px); top: calc(var(–scale-factor)*335.02px); font-size: calc(var(–scale-factor)*12.96px); font-family: serif; transform: scaleX(1.02313);" role="presentation">transformation strategy" <span dir="ltr" style="left: calc(var(–scale-factor)*189.43px); top: calc(var(–scale-factor)*335.02px); font-size: calc(var(–scale-factor)*12.96px); font-family: serif; transform: scaleX(1.03123);" role="presentation">and established their hierarchy; the key features of the strategy in <span dir="ltr" style="left: calc(var(–scale-factor)*56.66px); top: calc(var(–scale-factor)*352.06px); font-size: calc(var(–scale-factor)*12.96px); font-family: serif; transform: scaleX(0.997592);" role="presentation">the digital world are identified, namely: risk as the basis for development, people as the main <span dir="ltr" style="left: calc(var(–scale-factor)*56.66px); top: calc(var(–scale-factor)*368.88px); font-size: calc(var(–scale-factor)*12.96px); font-family: serif; transform: scaleX(1.02851);" role="presentation">business <span dir="ltr" style="left: calc(var(–scale-factor)*110.59px); top: calc(var(–scale-factor)*368.88px); font-size: calc(var(–scale-factor)*12.96px); font-family: serif; transform: scaleX(0.983297);" role="presentation">value <span dir="ltr" style="left: calc(var(–scale-factor)*147.23px); top: calc(var(–scale-factor)*368.88px); font-size: calc(var(–scale-factor)*12.96px); font-family: serif; transform: scaleX(1.03601);" role="presentation">and <span dir="ltr" style="left: calc(var(–scale-factor)*175.27px); top: calc(var(–scale-factor)*368.88px); font-size: calc(var(–scale-factor)*12.96px); font-family: serif; transform: scaleX(1.07794);" role="presentation">the <span dir="ltr" style="left: calc(var(–scale-factor)*201.16px); top: calc(var(–scale-factor)*368.88px); font-size: calc(var(–scale-factor)*12.96px); font-family: serif; transform: scaleX(1.02164);" role="presentation">formation <span dir="ltr" style="left: calc(var(–scale-factor)*262.02px); top: calc(var(–scale-factor)*368.88px); font-size: calc(var(–scale-factor)*12.96px); font-family: serif; transform: scaleX(0.946416);" role="presentation">of <span dir="ltr" style="left: calc(var(–scale-factor)*280.95px); top: calc(var(–scale-factor)*368.88px); font-size: calc(var(–scale-factor)*12.96px); font-family: serif; transform: scaleX(1.0632);" role="presentation">the <span dir="ltr" style="left: calc(var(–scale-factor)*306.61px); top: calc(var(–scale-factor)*368.88px); font-size: calc(var(–scale-factor)*12.96px); font-family: serif; transform: scaleX(1.04958);" role="presentation">right <span dir="ltr" style="left: calc(var(–scale-factor)*341.11px); top: calc(var(–scale-factor)*368.88px); font-size: calc(var(–scale-factor)*12.96px); font-family: serif; transform: scaleX(1.04226);" role="presentation">mindset <span dir="ltr" style="left: calc(var(–scale-factor)*392.90px); top: calc(var(–scale-factor)*368.88px); font-size: calc(var(–scale-factor)*12.96px); font-family: serif; transform: scaleX(0.924797);" role="presentation">of <span dir="ltr" style="left: calc(var(–scale-factor)*411.59px); top: calc(var(–scale-factor)*368.88px); font-size: calc(var(–scale-factor)*12.96px); font-family: serif; transform: scaleX(1.06435);" role="presentation">participants <span dir="ltr" style="left: calc(var(–scale-factor)*484.67px); top: calc(var(–scale-factor)*368.88px); font-size: calc(var(–scale-factor)*12.96px); font-family: serif; transform: scaleX(1.01895);" role="presentation">in <span dir="ltr" style="left: calc(var(–scale-factor)*503.84px); top: calc(var(–scale-factor)*368.88px); font-size: calc(var(–scale-factor)*12.96px); font-family: serif; transform: scaleX(1.03165);" role="presentation">digital <span dir="ltr" style="left: calc(var(–scale-factor)*56.66px); top: calc(var(–scale-factor)*385.92px); font-size: calc(var(–scale-factor)*12.96px); font-family: serif; transform: scaleX(1.03258);" role="presentation">transforma<span dir="ltr" style="left: calc(var(–scale-factor)*114.53px); top: calc(var(–scale-factor)*385.92px); font-size: calc(var(–scale-factor)*12.96px); font-family: serif; transform: scaleX(1.09789);" role="presentation">tion; the process of implementing the digital transformation strategy in the <span dir="ltr" style="left: calc(var(–scale-factor)*56.66px); top: calc(var(–scale-factor)*402.96px); font-size: calc(var(–scale-factor)*12.96px); font-family: serif; transform: scaleX(1.04209);" role="presentation">company is considered. The objective of the article was achieved through a review of the <span dir="ltr" style="left: calc(var(–scale-factor)*56.66px); top: calc(var(–scale-factor)*420.00px); font-size: calc(var(–scale-factor)*12.96px); font-family: serif; transform: scaleX(1.04594);" role="presentation">literature and the use of scientific methods, namely: comparative analysis, synthesis, and <span dir="ltr" style="left: calc(var(–scale-factor)*56.66px); top: calc(var(–scale-factor)*436.80px); font-size: calc(var(–scale-factor)*12.96px); font-family: serif; transform: scaleX(1.07859);" role="presentation">historical and logical methods. The results obtained contribute to the understanding of <span dir="ltr" style="left: calc(var(–scale-factor)*56.66px); top: calc(var(–scale-factor)*453.86px); font-size: calc(var(–scale-factor)*12.96px); font-family: serif; transform: scaleX(1.00467);" role="presentation">scientists and professionals about the development management process in the digital world.